2012
DOI: 10.1016/j.biortech.2012.02.082
|View full text |Cite
|
Sign up to set email alerts
|

Sequential solid-state and submerged cultivation of Aspergillus niger on sugarcane bagasse for the production of cellulase

Abstract: Sequential solid-state and submerged cultivation with sugarcane bagasse as substrate for cellulase production by Aspergillus niger A12 was assessed by measuring endoglucanase activity. An unconventional pre-culture with an initial fungal growth phase under solid-state cultivation was followed by a transition to submerged fermentation by adding the liquid culture medium to the mycelium grown on solid substrate. For comparison, control experiments were conducted using conventional submerged cultivation. The cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(61 citation statements)
references
References 29 publications
2
53
1
5
Order By: Relevance
“…The unconventional agitated pre-culture fermentation method (agitated-SmF) therefore had a positive influence on lignocellulolytic enzyme production, and similar results have been found for filamentous fungal morphological characteristics in submerged cultivations, which had an effect on cellulase production (Domingues et al 2000;Cunha et al 2012). Hence, this is the first work reporting on basidiomycetes using this pre-culture fermentation method and it has provided promising results.…”
Section: Effect Of Fermentation Methods On Production Of Lignocellulolsupporting
confidence: 66%
See 1 more Smart Citation
“…The unconventional agitated pre-culture fermentation method (agitated-SmF) therefore had a positive influence on lignocellulolytic enzyme production, and similar results have been found for filamentous fungal morphological characteristics in submerged cultivations, which had an effect on cellulase production (Domingues et al 2000;Cunha et al 2012). Hence, this is the first work reporting on basidiomycetes using this pre-culture fermentation method and it has provided promising results.…”
Section: Effect Of Fermentation Methods On Production Of Lignocellulolsupporting
confidence: 66%
“…Lignocellulolytic enzymes are currently produced by using either solid-state fermentation (SSF) or submerged fermentation (SmF) (Kang et al 2004;Singhania et al 2010;Farinas et al 2011). However, it seems that there have been few reports on lignocellulolytic enzyme production in submerged fermentation after a solid-state pre-culture step in fungi (Cunha et al 2012), and particularly no report in white rot fungi. There also have been no studies showing comparisons of lignocellulolytic enzyme production using various fermentation methods, including sequential solid-state and submerged fermentation, and conventional solid-state fermentation and submerged fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research reported that Aspergillus niger was produced 0.71 U/mL of xylanase activities after 30 hours' incubation times [17]. Comparison of seed culture conditions using different subculture of Pycnoporus sanguineus Based on the findings, comparisons between both subcultures were analyzed.…”
Section: Xylanase Enzymes Activitiesmentioning
confidence: 99%
“…However, the high hydrolysis costs are still a limiting factor for its industrial application (Cardona et al 2010). Thus, the search for new enzymes might improve the productivity and reduce costs in making the lignocellulose hydrolysis on industrial scale (Cunha et al 2012;Singhvi et al 2011). As regards the search for new industrial enzymes, the use of new strains may be an alternative method to improve the hydrolysis process.…”
Section: Introductionmentioning
confidence: 99%